"I'm Sorry + Naming the Offense": A Format for Apologizing. Issue 1 (2nd January 2016) - Cirillo, Letizia; Colón de Carvajal, Isabel; Ticca, Anna Claudia
Abstract : The present article focuses on "I'm sorry + naming the offense"–formatted apologies occurring in phone calls in English. Apologies of this kind "emerge" and are oriented to as relevant actions when addressing an apologizable that is not the main business in ongoing talk. The sequential analysis of apologies and responses to apologies suggest that the format "I'm sorry + naming the offense" relates to either minimal/potential offenses or even no offenses, that is, actions for which the apologizer's accountability is not visibly at stake. Therefore, the format thus identified seems to accomplish actions other than (just) apologizing, such as expressing regret or minimizing a compliment, ultimately being a fruitful resource to reinforce social solidarity.